The in vitro effect riboflavin combined with or without UVA in Acanthamoeba castellanii - Joohee Park; Choul Yong Park (Scientific Reports)
Abstract The anti-Acanthamoeba properties of riboflavin and its enhanced amoebicidal effects when combined with ultraviolet A (UVA) radiation were investigated in vitro. The viability of cultured Acanthamoeba castellanii was assessed by adding varying concentrations (0 ~ 0.2% w/v) of riboflavin to the culture medium or after combined riboflavin and UVA treatment (30 min, 3 mW/cm2) over 1, 3, 5, and 7 days. Intracellular reactive oxygen species (ROS) levels were measured following a 30-minute exposure to riboflavin. Additionally, the cysticidal effects of riboflavin, UVA, and their combination were evaluated. Gene transcription in Acanthamoeba was analyzed using RNA-seq. Riboflavin demonstrated dose-dependent toxicity on Acanthamoeba, accompanied by an increase in intracellular ROS. Exposure to 0.2% riboflavin reduced Acanthamoeba viability by over 50% within one day. UVA treatment alone also reduced viability by over 50%. Combined treatment with 0.2% riboflavin decreased trophozoite survival by more than 80%, and approximately 60% of cysts were killed when 0.1% riboflavin was combined with UVA. RNA-seq analysis indicated significant changes in gene expression after exposure to riboflavin, UVA, and their combination, particularly affecting oxidoreductase activity, cystathionine β synthase, and serine-threonine kinase activity. These findings indicate that riboflavin exhibits dose-dependent toxicity in Acanthamoeba, primarily through increased ROS generation. Combining riboflavin and UVA did not fully eradicate trophozoites and cysts of Acanthamoeba, but was able to partially inactivate them.